First-Order Stratigraphic Boundaries of the Late Cretaceous–Paleogene Retroarc Foreland Basin in Colombia - Carvajal-Torres, Juan; Catuneanu, Octavian; Mora, Andres; Caballero, Victor; Reyes, Martin (Frontiers in Earth Science, 2022)
The present-day Magdalena Valley, Eastern Cordillera, and Llanos Basin were part of a regional multiphase basin that started as an extensional basin in the Jurassic. Then, it was transformed into a retroarc foreland basin in the Late Cretaceous and subsequently separated into a hinterland and a foreland basin during the late Eocene. We incorporated new data from the Llanos Basin and Eastern Cordillera and chronostratigraphically correlated it with the adjacent basins. Their correlation contributed to establishing the stratigraphic boundaries formed during the first-order changes that marked the beginning and the end of the lifespan of the retroarc foreland basin. In the initial stage, the lateral extent along the dip of the significant depocenter that extended from the Magdalena Valley to the westernmost Llanos Basin was approximately 300–470 km. At the same time, the western flank of the Eastern Cordillera and most of the Llanos Basin were uplifting. The contact between the retrograding marine facies of the Upper Lidita, Buscavidas, Umir, Guadalupe, and Palmichal units marks a late Campanian maximum regressive surface formed during the initial exhumation of the orogen, the Central Cordillera. Therefore, it represents a first-order stratigraphic surface. This surface does not extend across the whole basin. In the uplifting areas, subaerial unconformities truncate the middle Campanian rocks. Their combination represents the lower first-order boundary of the sequence, and their diachroneity is the product of the northward migration of the orogen. The Teruel, Hoyon, Bogota, Cacho, Socha, Barco, and Cuervos formations are truncated by a regional subaerial unconformity. It was formed during orogenic unloading that marks the termination of the foreland basin in the Eocene. As it marks another first-order change, it is the upper boundary of the first-order sequence.